Estimating Risk to Humans Exposed to Highly Pathogenic Avian Influenza Outbreaks in the United States, 2014–2017. (4th October 2017) - Olsen, Sonja; Havers, Fiona; Rolfes, Melissa; Blanton, Lenee; Rooney, Jane; Gomez, Thomas; Nelson, Deborah; Karli, Steven; Trock, Susan C; Fry, Alicia M
Abstract: Background: In the USA, poultry outbreaks of highly pathogenic avian influenza viruses (AI) caused by H5 and H7 viruses have raised concern about the risk of infections in humans. Based on data from Asian lineage H5 and H7 AI, which sporadically transmit from poultry to humans, CDC currently recommends active daily monitoring of persons exposed to H5 and H7 AI viruses, including those who wear personal protective equipment (PPE). Methods: Persons exposed to HPAI-infected birds or contaminated environments in the USA were actively monitored during exposure and for 10 days post-exposure for illness, during 2014–2017. Some exposed persons were monitored on-site by USDA or contract safety officers, company staff, or state health officials. State health department staff monitored people during the 10-day post-exposure period. Persons reporting any respiratory illness or conjunctivitis were swabbed for molecular influenza testing. Preliminary results are presented. Results: From 2014 to 2017, 270 detections in poultry/wild birds were reported and at least 606 persons were potentially exposed to AI virus by exposure to birds, carcasses, or environment. Most exposed persons wore PPE. No human infections with AI viruses were detected. Conclusion: The risk of transmission of these H5 and H7 AI viruses to humans was low. These preliminary data offer evidence to change the recommendations for monitoring in persons exposed to these viruses. If final data support these findings, self-monitoring by workers with reporting to health departments if symptoms develop, rather than active monitoring by public health personnel, could be considered. However, it will be important to reconsider and update recommendations as the viruses evolve. Furthermore, risk of infection likely varies by exposure and those without PPE should be actively monitored. Disclosures: All authors: No reported disclosures.